Uso de parásitos en Hoplias malabaricus (characiformes: erythrinidae) como bioindicadores de salud ambiental a través de dinámicas tróficas en la laguna Huachana, Loreto- Perú - Cruz Guimaraes, José Lisbinio (2025)
Parasites are effective bioindicators of environmental health, reflecting ecosystem changes through their presence, diversity, and abundance. This study evaluated parasitic metazoans in Hoplias malabaricus "fasaco" from Huachana Lagoon, Iquitos, Loreto, to analyze their bioindicator potential. Between February and November 2024, 150 specimens of H. malabaricus were collected from three sites in Huachana Lagoon (five fish/site/month: 75 during the rising water level, 75 during the falling water level). As a control, 150 specimens were collected from Machín Lake (Allpahuayo Mishana National Reserve) following the same criteria. Diversity and richness were estimated using the Shannon-Wiener and Margalef indices (PAST 4.12), the ecto/endoparasite ratio was calculated using Excel, and the Species Indicator Value method (PAST 4.12) was used to identify characteristic species. The samples were processed at the IIAP's Parasitology and Aquaculture Health Laboratory. In Huachana Lagoon, three monogenoids (Urocleidoides brasiliensis, U. bulbophallus, and U. cuiabai) and two trematodes (Clinostomum marginatum and Icthyoclinostomum dimorphum) were identified. Analyses revealed low parasite diversity and richness, with an ecto to-endoparasite ratio of 10:1. The indicator species identified U. brasiliensis and U. bulbophallus as characteristic species suitable as bioindicators. Stomach content analysis showed that H. malabaricus acts as an intermediate host for C. marginatum and I. dimorphum. Comparatively, Machín Lagoon exhibited greater biodiversity, greater ecological richness, a 1:1 endo-to ectoparasite ratio, and a more interactive food web. These differences suggest a possible anthropogenic effect in the Huachana lagoon that conditions the trophic interactions of the ecosystem, validating the use of H. malabaricus parasites as bioindicators of environmental disturbance in Amazonian aquatic ecosystems.